6-5x=7x-3

Simple and best practice solution for 6-5x=7x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-5x=7x-3 equation:



6-5x=7x-3
We move all terms to the left:
6-5x-(7x-3)=0
We get rid of parentheses
-5x-7x+3+6=0
We add all the numbers together, and all the variables
-12x+9=0
We move all terms containing x to the left, all other terms to the right
-12x=-9
x=-9/-12
x=3/4

See similar equations:

| 2w+3w=7(8+2) | | -6x+6=-6(1-x) | | 6m1=85 | | 6x4-12x2=0 | | 5(x-6)=4x+4= | | 3x3=-3 | | 40-8w+4=6w-24+4w | | 16×22=y | | -2x+4(6+3x)=28+6x | | 2/3(3x+9=-2(2x+6) | | 10(n+2)=-150 | | 2x-1=2x-3 | | 18x−1=-19 | | 7/x=11/3 | | 2x+0=9x+8 | | 108=-6x-6 | | -3(h−8)=3 | | 3(2x+9)=-24+3 | | -a+4+3a=-4 | | -7x+8x=2x+4 | | 9x=10-3(5x-6) | | 4(3x+9)=-14+26 | | x(15+8+180+x)=13000 | | 18=3(k−11) | | 7/12=k/8 | | -8=-4(w−14) | | 6y+14=36 | | d+5d=12 | | 5u-8=-33 | | 3.5=x(x+3) | | 6z/7-5z/9=1 | | -8+p/3=-4 |

Equations solver categories